The Character Education According to Ki Hadjar Dewantara's View in Forming Gold Generations in The Era of Industrial Revolution 4.0 - Sanudin Ranam (Yayasan Ilomata, 2020)
The era of the industrial revolution 4.0 that is currently happening is marked by the rush of digitalization and automation which causes humans to not be separated from gadgets and the internet. Humans are subjects who play a role in regulating and determining that connectivity. People who have strong character will successfully develop connectivity in internet-based networks. Innovative, creative, honest, disciplined traits are required to exist in a network. That is why character education for our students is so necessary. Several research results show that the teachings and thoughts of Ki Hadjar Dewantara or Tamansiswa teachings are still very relevant to education today, this is because Ki Hadjar Dewantara teaches various things in shaping the character of the nation and is very down to earth and rooted in Indonesian culture, including Tutwuri Handayani, Pancadharma, Among, which is based on Trikon (continuity, convergence, and concentricity), Tripusat education (family, school, community), Tringga (Ngerti, Ngrasa, Nglakoni). Keywords: Industrial Revolution 4.0, Character Education, Ki Hadjar Dewantara